Predictive Analytics and Machine Learning in Healthcare: A Comprehensive Framework for Clinical Implementation - Rajendra Prasad Urukadle, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Predictive analytics and machine learning models are revolutionizing healthcare management by enabling proactive intervention strategies through sophisticated data analysis. This article explores the integration of machine learning algorithms with historical health data to forecast potential health events and risks, providing healthcare providers with powerful tools for anticipatory care. Examining the fundamental architecture, implementation challenges, and clinical validation methods of these predictive models, it demonstrates their transformative impact on healthcare delivery. This article highlights the importance of robust model development, seamless clinical workflow integration, and adherence to regulatory requirements while addressing critical concerns regarding data privacy and ethical considerations. It suggests the successful deployment of predictive analytics in healthcare settings can significantly enhance patient outcomes and resource allocation efficiency while establishing a framework for future advancements in personalized medicine.
Keywords: Predictive Analytics; Healthcare Machine Learning; Clinical Decision Support; Risk Forecasting; Proactive Healthcare Management